2018
DOI: 10.4014/jmb.1801.01012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Antioxidant Activity of the Exopolysaccharide Produced by Bacillus amyloliquefaciens GSBa-1

Abstract: The exopolysaccharide (EPS) produced by Bacillus amyloliquefaciens GSBa-1 was isolated and purified by ethanol precipitation, DEAE-cellulose and Sepharose CL-6B chromatography. The molecular weight of the purified EPS was determined to be 54 kDa. Monosaccharide analysis showed that the EPS was composed of predominantly glucose, and it was further confirmed by NMR spectroscopy to be α-glucan consisted of a trisaccharide repeating unit with possible presence of two α-(1→3) and one α-(1→6) glucosidic linkages. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 49 publications
4
12
0
Order By: Relevance
“…The hydroxyl free radical scavenging results of the exopolysaccharide in the potent isolate of B. amyloliquefaciens was 89.75 ± 2.68%. The bacterial exopolysaccharides have free radical scavenging abilities on both DPPH radicals and hydroxyl radicals with various bioactivities viz , prevention of chain initiation, decomposition of peroxides ( Zhao et al, 2018 , Wang et al, 2017 ). The previous findings are in accordance with our reports which reveal the H 2 O 2 free radical scavenging results of EPS from the candidate isolate was 68.65 ± 0.22%.…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxyl free radical scavenging results of the exopolysaccharide in the potent isolate of B. amyloliquefaciens was 89.75 ± 2.68%. The bacterial exopolysaccharides have free radical scavenging abilities on both DPPH radicals and hydroxyl radicals with various bioactivities viz , prevention of chain initiation, decomposition of peroxides ( Zhao et al, 2018 , Wang et al, 2017 ). The previous findings are in accordance with our reports which reveal the H 2 O 2 free radical scavenging results of EPS from the candidate isolate was 68.65 ± 0.22%.…”
Section: Discussionmentioning
confidence: 99%
“…The 1 H NMR spectrum ( Figure 5 ) displayed the characteristic anomeric (H1) signals in the anomeric region 4.0–5.4 ppm. In this anomeric region, a doublet was found at 4.55 ppm and another doublet was found at 4.58 ppm and these two peaks were identified β- d -Galactopyranose (β- d -Gal p ), which should contain a linkage at its 6th/2nd position, and a Terminal (0) β- d -Gal p [ 69 ]. Since these peaks are slightly overlapped with the water signal, the intensities are incorrect and not shown in the figure (Magnified portion).…”
Section: Resultsmentioning
confidence: 99%
“…Most lactobacillus EPS molecules are heteropolymers consisting of repeated copies of oligosaccharide units [15]. EPS, which are produced either intracellularly or extracellularly, contribute to biological activity via specific composition, size, and branching structure, which can differ even among members of the same LAB strain [33].…”
Section: Discussionmentioning
confidence: 99%
“…Exopolysaccharide (EPS) consists of long-chain polysaccharides with various branches and repeating units of sugars or sugar derivatives [15]. Recent studies showed that EPS from marine microorganisms has potential applications as a therapeutic food [12,16].…”
Section: Introductionmentioning
confidence: 99%